Methodological proposal for design at the conceptual level for quality improvement: an application at the infrastructure of CETEC/UPF - Becker, Alcione Carvalho (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
With the objective of assisting in the process of designing Civil Engineering and Architecture infrastructure projects, this article presents a research that was carried out in the areas of Production and Mechanics Engineering in order to look for techniques and methodologies for the development of industrial products. Following the analysis of tools, such as Value Engineering (VE) and Quality Function Development (QFD), a methodology for the development of infrastructure conceptual product design has been proposed. The methodology was applied in the design of the Technological Center of Civil and Environmental Engineering and Architecture of University of Passo Fundo. The results have shown that the proposed methodology helps in the development of infrastructure design process, allowing the development of alternative strategies, and provide quantitative elements for the adoption of the product conception suggested by the target users.